Competição de 10 gramíneas para capineiras, no cerrado, em 1965 - Mauro A Pereira, R; J Sykes, D; Gomide, J A; T Vidigal, G (Revista Ceres, 2025)
In Prudente de Morais, Minas Gerais Brazil, 10 varieties ofgreen-chop grasses were studied during the rainy summer and during the winter dry season of 1965 with and without fertilization. Cutting was based on the phenological development of the grasses, corresponding to seed-head emergence. Pennisetum purpureum varieties Mercker and Napier tended to out-yield all other varieties in total green matter product on in both the rainy season and the dry season. Fertilization during the summer caused an increase in green matter production of only 11. 8% over check plots. However dry season fertilization when not irrigated resulted in a slight decrease in production. Plots irrigated during the dry season showed a green matter production 70% higher thanplots not irrigated nor fertilized. A satisfactory response was obtained by combining irrigation and fertilizationwhich increased forrage production by 169% over the check plots.